DYNAMIC ANALYSIS OF DOUBLE COMPOSITE BEAM WITH MOVING MASS - ZHAO Liang; LIU LiHua (Jixie qiangdu)
The simply supported double composite beam with moving mass is investigated. During the analysis,the acceleration of the moving mass can be arbitrary. With some assumptions, the strain energy and the kinetic energy of the system are gotten. Then the axial-bending coupled equations of motion are derived by the Hamilton’s principle, and solved by the finite element method combined with Newmark method. The numerical examples show that, the larger the speed of moving mass the larger the maximum vertical displacement of the beam; the horizental displacement of centre point of the beam is zero when the moving mass on the centre point; under the same conditions, the double composite beams have higher stiffness-to-weight ratio than the single layer ones. The conclusions obtained here provide theoretical references for designing the structures with high strength and light weight.